Enseñanza - color - País Vasco: claves de una reflexión (ávida de esperanza) - Preciado Sáez de Ocáriz, Txema (Arte, Individuo y Sociedad, 2007)
This article revolves around the initial components of the title -a professional situation, a topic being studied and a socio cultural context with the Basque language as its outstanding protagonist - and it aims, faced with the vigour of the ’universalist’ (or Western mentality’s) outline of perception, comprehension and articulation of the world of colour which tends to build itself up as the main (if not the only) reference guideline, claiming responsibility for its cultural dimension by raising awareness of the Basque situation, with particular reference to schools.